Poster - Switch off Saturday - Campaign Against Pit Closures, 1992 (1992)
1992 1960-2000 "Poster - Switch off Saturday - Campaign Against Pit Closures, 1992" [T0544.jpg], 1992 On October 13, 1992, the Government announced that 31 of British Coals remaining pits would close with the loss of 30,000 jobs. The National Union of Mineworkers launched a campaign against the closures which gained widespread public support, but which in the end was generally unsuccessful in securing the future of the coal industry. There were two massive demonstrations in London on October 21 and 25 and a mass lobby in Central Hall Westminster. In December, the Scottish Area NUM organised a march to London and a Switch Off campaign, urging people to turn off their lights for five minutes at 8pm on December 19.